Alphaherpesvirus glycoprotein E: A review of its interactions with other proteins of the virus and its application in vaccinology - Ning, Yaru; Huang, Yalin; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Wu, Ying; Tian, Bin; Ou, Xumin; Huang, Juan; Mao, Sai; Sun, Di; Zhao, Xinxin; et al. (Frontiers in Microbiology, 2022)
The viral envelope glycoprotein E (gE) is required for cell-to-cell transmission, anterograde and retrograde neurotransmission, and immune evasion of alphaherpesviruses. gE can also interact with other proteins of the virus and perform various functions in the virus life cycle. In addition, the gE gene is often the target gene for the construction of gene-deleted attenuated marker vaccines. In recent years, new progress has been made in the research and vaccine application of gE with other proteins of the virus. This article reviews the structure of gE, the relationship between gE and other proteins of the virus, and the application of gE in vaccinology, which provides useful information for further research on gE.